What do I need to get there? Wayfinding system for hospital complex - Smythe, Kelli C.A.S.; Cherubini, Nadaly G. (InfoDesign, 2023)
The difficulty of spatial orientation in cities and built environments affects different profiles of people and different ways people search for information to orient themselves. The design of wayfinding systems is the main help in this orientation, so this paper aims to present the development of a wayfinding system, by undergraduate students, for a university hospital, using the Wayfinding Information Behavior method. First, concepts and descriptions of spatial cognition, information behavior, and wayfinding system design are presented. The configuration and application of the data collection method is then described, followed by a brief description of the design steps used by the students. The alternatives obtained are then presented and the main points resulting from the use of the method are discussed. With the results obtained, it is possible to note the potential of the method as a relevant data collection tool for projects of this type.